Criminal Policy on Countering Organized Crime Against Land Ownership in the Perspective of Criminal Law Reform - Yuda Pratama Darmawan; Lies Suetani; Yani Pujiwati (Justisi)
This research aims to analyze the countermeasures of organized criminal acts related to land ownership in Indonesia and analyze criminal policies to overcome these criminal acts in the future from the perspective of criminal law reform.